21ST CENTURY EDUCATIONAL TRANSFORMATION: INNOVATIONS AND CHALLENGES IN TEACHING AND LEARNING - Rusydi Rusydi; Loso Judijanto; St. Wijdanah Ram (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Education in the 21st century is undergoing major changes. Advances in technology and the demands of a globalised world mean that the way we learn and teach must change. The research method in this study uses literature. The results show that today, many schools are starting to use technology in the classroom. Teachers are also changing the way they teach so that students are more active learners. Students need to learn new skills to succeed in the future. Despite the progress, there are still many challenges. Not all students have access to technology. Many teachers need training to use new methods. The curriculum also needs to be updated. To overcome these problems, all parties must work together. The government, schools, teachers and parents need to come together to make education better. With joint efforts, we can create an education system that is ready for the future.